May Financial Literacy, Risk Tolerance, and Demographic Factors Influence the Investment Decisions of BCA Malang Customers? - Lulu Nurul Istanti; Ninuk Puji Lestari (Asean International Journal of Business, 2023)
Purpose – This research aims to show empirically that financial literacy, risk tolerance, and demographic factors directly influence the investment decisions of Bank BCA Malang, Indonesia, customers. Methodology/approach – The purpose sampling method in this study has specific criteria in sampling, namely customers who are at least 17 years old, have invested at least one year, and have their income. This study shows the direct impact of using SEM-PLS analysis to demonstrate the dependence of independent variables on investment decisions. Findings – The analysis results show that financial literacy does not affect investment decisions. Furthermore, the results of the hypothesis testing analysis carried out explain that risk tolerance affects investment decisions. Finally, the hypothesis testing analysis results explain that the variables of demographic factors do not affect investment decisions.